(untitled) (Revista Brasileira Multidisciplinar, 2021)
This work aimed to evaluate the approach of environmental themes by teachers of Elementary School I, with training in Pedagogy, from the municipal network of the city of Maringá-PR. As a source of data collection, semi-structured questionnaires were developed and applied, with open and closed questions, to 30 teachers. The data were organized into categories seeking to establish similarities and differences, which could establish a profile of the schools studied and which indicated the approach to environmental issues in the schools under study. The Municipal Secretary of Education of Maringá, as the official teaching body, seeks to favor the performance of the teacher in the face of discussions on environmental issues. The surveyed schools present similar environmental themes and pedagogical practices, regardless of their location, population served and initial training of their teachers. We found in our analysis that these subjects are not efficiently addressed in class and are usually presented on punctual dates. Teachers find it difficult to discuss environmental issues in an interdisciplinary way because they are not adequately prepared for the application of these contents. In an attempt to justify their unpreparedness, they point out difficulties in relation to the student, the school infrastructure and school plans, and at the same time present many ambiguities regarding these themes. Interdisciplinarity is not contemplated and the topics discussed in schools are usually addressed by science teachers.